Human Existence In Harriet Beecher Stowe's Uncle Tom's Cabin:An Existentialist Approach - Cipta, Kiki Eka Mira (2004)
In this study, the researcher attempts to identify the human existence reflected in Harriet Beecher Stowe's Uncle Tom's Cabin. The objective of the study is to analyze the structural elements of Uncle Tom's Cabin and to analyze the literary work based on the existentialist perspective. In analyzing Uncle Tom's Cabin, the writer uses the existentialist approach and qualitative method. The object of the research is the aspect of existentialism in Stowe's novel, published in 1909 by Everyman's Library. The data are literary ones that are divided into two categories: primary and secondary data. The primary data source is from the novel of Uncle Tom's Cabin itself. While secondary data sources are from the books about existentialist and the other materials, which related to the analysis. The method of data collection technique of this research is the library research. The data analyzing technique is using descriptive technique. The result of the study is that human existence in Stowe's Uncle Tom's Cabin is reflected through characters and characterization, plot and theme. Stowe's gives the biggest attention on the human freedom to decide their choices based on their own will. Stowe and existentialist believe that this freedom is important to reach existence, because freedom is the core of human existence.